Cellular antioxidant activity and in vitro inhibition of α-glucosidase, α-amylase and pancreatic lipase of oregano polyphenols under simulated gastrointestinal digestion. (February 2019) - Gutiérrez-Grijalva, Erick P.; Antunes-Ricardo, Marilena; Acosta-Estrada, Beatriz A.; Gutiérrez-Uribe, Janet A.; Basilio Heredia, J.
Abstract: Different oregano species have been traditionally used as infusions in folk medicine. Oregano medicinal properties, such as antioxidant and anti-inflammatory, have been partially attributed to its polyphenolic content. However, information regarding bioaccessibility of oregano polyphenols is limited. Cell-based antioxidant activity, and in vitro hypoglycemic, and hypolipidemic properties of polyphenolic extracts from three species of oregano species, namely, Hedeoma patens (HP), Lippia graveolens (LG) and Lippia palmeri (LP), subjected to simulated gastrointestinal digestion were evaluated. LC-TOF-MS analysis of HP, LG and LP allowed the identification of 9 flavonoids and 6 hydroxycinnamic acid derivatives with nutraceutical significance. Oregano polyphenolic extracts and digests from HP, LG, and LP exhibited cellular antioxidant capacity, hypoglycemic and hypolipidemic properties. Altogether, our results suggest that HP, LG and LP polyphenols exhibit potential for use as hypoglycemic, hypolipidemic, and antioxidant agents. Graphical abstract: Unlabelled Image Highlights: Cellular antioxidant activity of oregano polyphenols is enhanced after digestion. Oregano polyphenols show higher α-glucosidase inhibition than acarbose. Oregano polyphenols showed lower inhibition of α-amylase than acarbose. Lipase inhibition of polyphenols from oregano is enhanced after digestion.